Initiating hybrid closed loop: A program evaluation of an educator‐led Control‐IQ follow‐up at a large pediatric clinic. Issue 4 (16th March 2021) - Messer, Laurel H.; Berget, Cari; Ernst, Ashlee; Towers, Lindsey; Slover, Robert H.; Forlenza, Gregory P.
Abstract: Background: Control‐IQ (Tandem Diabetes) is a hybrid closed‐loop (HCL) system that users self‐initiate after completing online training. Best practices for clinical follow‐up are not known. Our quality improvement objective was to evaluate the usefulness of an educator‐led follow‐up program for new HCL users in a type 1 diabetes pediatric clinic. Methods: We implemented an ''HCLCheck‐in'' program, first determining when users started HCL, then having diabetes educators contact them for a follow‐up call 2‐weeks after start. Educators used a Clinical Tool to inform insulin dose and behavior recommendations, and used four benchmarks to determine need for further follow‐up: ≥71% HCL use, ≥71% CGM use, ≥60% Time‐in‐Range (TIR, 70–180 mg/dL), <5% below 70 mg/dL. Family and educator satisfaction were surveyed. Results: One‐hundred‐twenty‐three youth [mean age 13.6 ± 3.7 y, 53.7% female, mean HbA1c 7.6 ± 1.4% (60 mmol/mol)] completed an HCLCheck‐in call a median (IQR) of 18(15, 21) days post‐HCL start. 74 users (60%) surpassed benchmarks with 94% HCL use and 71% TIR. Of the 49 who did not, 16 completed a second call, and improved median TIR 12.5% (p = 0.03). HCL users reported high satisfaction with the program overall [median 10 (9, 10) out of 10]. Educators spent a median of 45 (32, 70) minutes per user and rated satisfaction with the program as 8 (7, 9.5) and the Tool as 9 (9, 10). Conclusion: Our HCLCheck‐in program received high satisfaction ratings and resulted in improved TIR for those initially not meeting benchmarks, suggesting users may benefit from early follow‐up. Similar programs may be beneficial for other new technologies.